Anti-proliferative activity of crude and fractionated extract of labisia pumila on human prostate cancer cell lines - Jamaludin, Nurhikmah (2016)
Labisia pumila (L. pumila) or locally known as Kacip Fatimah has been widely used by women in Malaysia to address post-partum health conditions. This herbaceous undershrub of the Myrsinaceae family has been made into beverages, cosmetics health and supplements to promote overall wellness. The objective of the present study was to determine the anti-proliferative property of L. pumila crude extract against prostate cancer cell lines. In this study, the crude extract was prepared by using ultrasound assisted extraction method. The result revealed that L. pumila crude extract inhibited the proliferation of the prostate cancer cell lines. The crude extract was further fractionated using column chromatography and the most active fraction was determined as 40% methanol (MeOH) fraction. The results showed that both crude extract and 40% MeOH fraction contained phytochemicals that caused the characteristic apoptosis. However, higher percentage of early and late apoptosis were observed in crude extract as compared with 40% MeOH fraction. As for the apoptotic body, this characteristic was only found in the DU 145 prostate cancer cell morphology that was treated with 40% MeOH fraction. The result from the scavenging activity test confirmed that L. pumila crude extract and 40% MeOH fraction displayed a strong antioxidant activity with the value of 70%. Total phenolic contents assay was carried out to determine the phenolic content of the extract and its active fraction. Identification on polyphenolic compound was carried out using Ultraperformance liquid chromatography tandem mass-spectrometry and the result revealed that rutin and 3 organic acids including gallic, p-coumaric and salicylic acids were present in both crude extract and 40% MeOH fraction. High performance liquid chromatography analysis confirmed that gallic acid as one of the phytochemical constituents found in L. pumila. In conclusion, these findings suggested that crude extract and 40% MeOH fraction of L. pumila contains phenolic compound that act as an anti-proliferative agent against proliferation of prostate cancer cell lines in vitro.